2017
DOI: 10.1037/xlm0000395
|View full text |Cite
|
Sign up to set email alerts
|

Free recall test experience potentiates strategy-driven effects of value on memory.

Abstract: People tend to show better memory for information that is deemed valuable or important. By one mechanism, individuals selectively engage deeper, semantic encoding strategies for high value items (Cohen et al., 2014). By another mechanism, information paired with value or reward is automatically strengthened in memory via dopaminergic projections from midbrain to hippocampus (Shohamy & Adcock, 2010). We hypothesized that the latter mechanism would primarily enhance recollection-based memory, while the former me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
65
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(78 citation statements)
references
References 59 publications
(117 reference statements)
11
65
2
Order By: Relevance
“…It seems unlikely that 1 s of encoding was enough to fully use more complex elaborative strategies such as mental imagery or putting items into a sentence. Although studies involving multiple study-test lists with feedback find that participants selectively apply elaborative strategies based on itemvalue (Ariel, Price, & Hertzog, 2015;Cohen et al, 2017) it may be that such differences in elaboration are less pronounced when learning a single list without intermittent feedback. This feedback may help them develop more selective encoding strategies (Cohen et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It seems unlikely that 1 s of encoding was enough to fully use more complex elaborative strategies such as mental imagery or putting items into a sentence. Although studies involving multiple study-test lists with feedback find that participants selectively apply elaborative strategies based on itemvalue (Ariel, Price, & Hertzog, 2015;Cohen et al, 2017) it may be that such differences in elaboration are less pronounced when learning a single list without intermittent feedback. This feedback may help them develop more selective encoding strategies (Cohen et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…These elaborative strategies use deeper semantic and associative processing, which produces a stronger memory trace (Craik & Lockhart, 1972;Richardson, 1998). In Cohen, Rissman, Hovhannisyan, Castel, and Knowlton (2017), a large proportion of participants also reported using different mnemonic strategies based on item-value. Interestingly, many of these participants reported that they did not even attempt to selectively learn valuable items, but despite this supposed indifference to value, they still exhibited better memory for valuable material.…”
Section: Potential Mechanisms Supporting Value-directed Rememberingmentioning
confidence: 99%
See 1 more Smart Citation
“…The agenda-based regulation framework posits that time, resources, and effort are allocated based on a goal-oriented agenda that aims to maximize performance (Ariel et al, 2009;Dunlosky and Ariel, 2011;Middlebrooks et al, 2017). In accordance with this framework, both older and younger adults typically report selectively using elaborative semantic encoding strategies when learning valuable items (Ariel et al, 2015;Cohen et al, 2017). In the present dataset, 16 of 23 older adults and 14 of 19 young adults reported using strategies related to the meanings of the words to support encoding (see the supplemental material of Cohen et al, 2016, for a full description of these self-report data).…”
Section: Discussionmentioning
confidence: 99%
“…This preserved ability to selectively engage semantic strategies during encoding was interpreted to underlie older adults' preserved ability to preferentially encode high-value items in the VDR task. Other studies have further explored participants' ability to selectively attend to high-value items (Ariel et al, 2015;Robison and Unsworth, 2017) and use more effective learning strategies that involve associative and semantic processing (Ariel et al, 2015;Cohen et al, 2017). These learning strategies are thought to produce a deeper and more elaborative encoding of semantic information that has been shown to improve memory performance (Craik and Tulving, 1975;Richardson, 1998).…”
mentioning
confidence: 99%